A Note on Nearly Quasi-Einstein Manifolds (European Journal of Pure and Applied Mathematics, 2012)
The object of the present paper is to study nearly quasi-Einstein manifold. Also we haveÂ studied decomposable Riemannian manifold and it is shown that a decomposable Riemannian manifoldÂ is nearly quasi-Einstein if and only if both the decompositions are Einstein.